STRATEGI PEMBELAJARAN GURU Implementasi dan Implikasinya terhadap Prestasi Belajar Siswa (Studi Kasus di Madrasah Ibtida’iyah Mambaul Ulum Bata-Bata Madura) - Moh. Hafidurrahman (Kuttab : Jurnal Ilmu Pendidikan Islam, 2017)
Educational activities require good steps in producing qualified students. Recognizing the importance of the teacher's role in education, in the modern era, teachers are not only teaching individuals but are also directors of learning. That means every teacher is expected to be brilliant to direct the learning activities of students to achieve a learning success. As a consequence, the teacher's tasks and responsibilities become more complex. The expansion of these tasks and responsibilities brings the consequences of the emergence of special functions that serve as an integral part of the teacher's professionalism competence in dealing with the classroom conditions. Therefore, a teacher is required to be really extra in preparing lessons and strategies. The effort is done because it is realized that education is an effort to develop all potentials of students to be able to keep up with the rapid development of science through the selection of materials, methods and instructional media, as well as appropriate teaching system.Keywords: Learning strategy, Teacher, Learning achievement